Interaction of membrane cholesterol with GPCRs: implications in receptor oligomerization - Sengupta, D.; Kumar, G. A.; Chattopadhyay, A. (Receptors, 2017)
G protein-coupled receptors (GPCRs) are the largest family of proteins involved in signal transduction across cell membranes, and represent major drug targets in all clinical areas. Oligomerization of GPCRs and its implications in drug discovery constitute an exciting area in contemporary biology. In this review, we have highlighted the role of membrane cholesterol and the actin cytoskeleton in GPCR oligomerization, using a combined approach of homo-FRET and coarse-grain molecular dynamics simulations. In the process, we have highlighted experimental and computational methods that have been successful in analyzing different facets of GPCR association. Analysis of photobleaching homo-FRET data provided novel information about the presence of receptor oligomers under varying conditions. Molecular dynamics simulations have helped to pinpoint transmembrane helices that are involved in forming the receptor dimer interface, and this appears to be dependent on membrane cholesterol content. This gives rise to the exciting and challenging possibility of age and tissue dependence of drug efficacy. We envision that GPCR oligomerization could be a game changer in future drug discovery.